2020
DOI: 10.15171/jlms.2020.10
|View full text |Cite
|
Sign up to set email alerts
|

Low-Level Laser Effect on Peripheral Sciatic Regeneration Under the Systemic Inflammatory Condition of Periodontal Disease

Abstract: Introduction: Periodontal disease (PD) is an inflammatory condition, which leads to tooth loss and promotes a systemic inflammatory state that can aggravate the nerve degeneration. As laser therapy may stimulate regeneration, this study aimed to evaluate the effect of the low-level laser (LLL) on peripheral nerve regeneration under the systemic inflammatory condition of PD. Methods: Thirry-two male rats were used, distributed in 4 groups: nerve injury (NIG); periodontal disease with nerve injury (PDNI); nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The aim of this treatment is to induce regeneration of cells, as it acts on the fibroblastic proliferation and moreover has a direct effect on the Schwann cells, which has an anti-inflammatory role and secretes neurotrophic effect for nerve regeneration. A study by Malanotte et al ,[ 28 ] and a similar study in experimental animal model showed that in mice induced with periodontal disease and nerve injury, the degree of nerve regeneration showed promising results, but the inflammatory component had not reduced. Furthermore, the study showed protection of cells against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this treatment is to induce regeneration of cells, as it acts on the fibroblastic proliferation and moreover has a direct effect on the Schwann cells, which has an anti-inflammatory role and secretes neurotrophic effect for nerve regeneration. A study by Malanotte et al ,[ 28 ] and a similar study in experimental animal model showed that in mice induced with periodontal disease and nerve injury, the degree of nerve regeneration showed promising results, but the inflammatory component had not reduced. Furthermore, the study showed protection of cells against oxidative stress.…”
Section: Discussionmentioning
confidence: 99%